PREVALENCE AND RISK FACTORS OF IODINE DEFICIENCY AMONG RURAL ANTENATAL MOTHERS IN BACHOK, KELANTAN - Noran H; Zulkifli A; Naing L; Mafauzy M (Malaysian Journal of Public Health Medicine, 2005)
Iodine is an essential micronutrient for normal physical and mental development. Iodine deficiency is endemic in 130 countries worldwide, including Malaysia. This is a cross-sectional study done to determine the prevalence and risk factors of iodine deficiency among 342 rural mothers attending antenatal clinics in Bachok, Kelantan. A self-administered questionnaire on the knowledge, attitudes, practices, and other risk factors relating to iodine deficiency was done. A physical examination for thyroid enlargement was carried out and urine samples were taken for urine iodine determination. The prevalence of iodine deficiency based on urine iodine levels of less than 100 mcg/l was 63.0 % (95% CI: 57.8, 68.2). The mean urinary iodine level was 87.3 mcg/l with a median of 78.0 mcg/l. However, the goiter prevalence was only 9.4%. The total mean scores of knowledge, attitudes and practices were generally low at 58.6 (SD 7.9), 52.9 (SD 7.9) and 42.9 (SD 10.9) respectively. Logistic regression analysis found that a smoking husband is a risk for iodine deficiency (OR=2.0). In conclusion, iodine deficiency disorders among rural antenatal mothers were still prevalent in Bachok. Their level of knowledge on the causes, effects, prevention and clinical presentations of iodine deficiency disorders were poor. In addition, having a husband who is a smoker increases the risk of the antenatal mothers developing iodine deficiency.